Pest control: how to get it right - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Managing Pests and Pesticides in Small-Scale Agriculture by F H J Schoubroeck M Herens, W de Louw, J M Louwen, T Overtoom, translated by J Elington, FH J Schoubroeck and J M Louwen, 204pp, 1990, ISBN 90 70857 18 9, published by CON and available from TOOL